Your question is a difference of squares. both terms that need to be factored are squared. to solve take the square root of each put into two terms one of addition and one of subtraction.
anwser= (5x-9)(5x+9)
the reason this works is because when you foil you get
25x²-45x+45x-81
the middle terms cancel revealing
25x²-81
Answer:
The answer to your question is No
Step-by-step explanation:
Data
function f(x) = 2x³ + x² - 10x - 12
To know if a number is a root of a function, evaluate the function on that number, if the result is zero, then that number is a root.
Substitution
f(-2) = 2(-2)³ + (-2)² - 10(-2) - 12
Simplification
f(-2) = 2(-8) + 4 + 20 - 12
f(-2) = -16 + 4 + 20 - 12
f(-2) = -28 + 24
f(-2) = -4
-2 is not a root that the function.
1) Midpoint : (7/2,1/2), Quadrant 1
2. Midpoint: (5,1/2), Quadrant 2
Hope this helps. Please mark brainliest if you can
11. Factoring and solving equations
- A. Factor-
1. Factor 3x2 + 6x if possible.
Look for monomial (single-term) factors first; 3 is a factor of both 3x2
and 6x and so is x . Factor them out to get
3x2 + 6x = 3(x2 + 2x1 = 3x(x+ 2) .
2. Factor x2 + x - 6 if possible.
Here we have no common monomial factors. To get the x2 term
we'll have the form (x +-)(x +-) . Since
(x+A)(x+B) = x2 + (A+B)x + AB ,
we need two numbers A and B whose sum is 1 and whose product is
-6 . Integer possibilities that will give a product of -6 are
-6 and 1, 6 and -1, -3 and 2, 3 and -2.
The only pair whose sum is 1 is (3 and -2) , so the factorization is
x2 + x - 6 = (x+3)(x-2) .
3. Factor 4x2 - 3x - 10 if possible.
Because of the 4x2 term the factored form wli be either
(4x+A)(x +B) or (2x+A)(2x+B) . Because of the -10 the integer possibilities
for the pair A, B are
10 and -1 , -10 and 1 , 5 and -2 . -5 and 2 , plus each of
these in reversed order.
Check the various possibilities by trial and error. It may help to write
out the expansions
(4x + A)(x+ B) = 4x2 + (4B+A)x + A8
1 trying to get -3 here
(2x+A)(2x+B) = 4x2 + (2B+ 2A)x + AB
Trial and error gives the factorization 4x2 - 3x - 10 - (4x+5)(x- 2) .
4. Difference of two squares. Since (A + B)(A - B) = - B~ , any
expression of the form A' - B' can be factored. Note that A and B
might be anything at all.
Examples: 9x2 - 16 = (3x1' - 4' = (3x +4)(3x - 4)
x2 - 29 = x2 - (my)* = (x+ JTy)(x- my)
Answer:
x^2
Step-by-step explanation:
x^5 = x*x*x*x*x
x^2 = x*x
The greatest common factor is x*x or x^2